A Laboratory Investigation on the Effects of Intermittent Water Supply and Remedial Measures - Marco Ferrante; Dewi Rogers; Josses Mugabi; Francesco Casinini (Water Resources Research)
Abstract The intermittent water supply (IWS) of water distribution systems is a common practice caused by the imbalance between available water resources and customers' demands. Transition to the continuous water supply (CWS) is desirable to reduce quality, equity distribution, and pipe integrity issues but is often practically unachievable in the short or medium term. The World Bank funded a laboratory activity at the Water Engineering laboratory of the University of Perugia, Italy, to investigate how remedies can be introduced to mitigate the impacts of IWS and preserve pipe integrity, facilitating the transition from IWS to CWS. The results of the tests with different feeding conditions, downstream outflows, and air valve dimensions and locations are described and discussed in this paper, culminating in typical interventions that can be implemented to reduce, if not completely eliminate, the undesirable consequences.